Composition of sulfur species in deasphalted oils and their molecular-level transformation during the hydrotreating process. (15th November 2022) - Chen, Zhentao; Wang, Yuanfeng; Wu, Jianxun; Wang, Bo; Jiang, Tao; Yu, Jiahuan; Yang, Haoxuan; Zhao, Suoqi; Shi, Quan; Xu, Chunming
Highlights: DAOs are separated into subfractions combining methylation and solvent extraction. HDS chemistry of DAOs is unraveled by combining conversion and composition analysis. Sulfides and thiophenes have similar reactivity but different evolution chemistry. Polar fractions are refractory due to the unreactivity and inhibitors existing in them. Abstract: The sulfur removal chemistry is critical to the efficient conversion of heavy oils. The compositions and HDS reactivities of sulfur-containing compounds in two deasphalted oils were systematically investigated by electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FT-ICR MS) combined with a self-established separation method. The deasphalted oils are separated into three subfractions by a combination of methylation/demethylation and solvent extraction. The S1 class sulfur compounds with low and high DBE (double bond equivalent) values dominated the sulfidic and thiophenic subfractions, respectively, while polyheteroatomic compounds are the major components in the polar subfractions. Three sulfur subfractions exhibited different reactivities under the same hydrotreating conditions. The sulfidic and thiophenic subfractions have similar HDS reactivities, and the sulfur species with low and high DBE values are preferentially removed from the above subfractions, respectively. Sulfur compounds in the polar subfractions are the least reactive species, resulting from the existed unreactive sulfur components and the inhibition of polyaromatics and nitrogen-containing compounds. This study represents an advance in unraveling the complex desulfurization chemistry in heavy oils, and facilitates the development of superior hydrodesulfurization catalysts.